AC Power Flow-Based Co-Optimization for Integrated Generation and Transmission Network Expansion Planning - Chillogalli, José E. [UNESP] (2024)
The integrated Generation and Transmission Network Expansion Planning (GTNEP) models have been developed to enable simultaneous investment decisions that consider both investment and operational components. In this research, a new methodology to assess the GTNEP is proposed, which takes into account the integrated planning of new generation power plants, transmission lines, reactive power allocation, and network power losses. To address the GTNEP, the operational problem is formulated using the AC optimal power flow, providing more realistic solutions. As a solution method, the Iterated Greedy Algorithm (IGA), and a hybridization of differential evolution with the tabu search (DE-TS) meta-heuristic were implemented. The proposed approach was tested using the 6-bus Garver test system. The results demonstrate that more cost-effective and realistic expansion plans are found with integrated AC-GTNEP compared to the sequential approach of first solving Generation Expansion Planning (GEP), and then Transmission Network Expansion Planning (TNEP).